2014
DOI: 10.1093/jncimonographs/lgu029
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy in Real and Sham Electroacupuncture: Does Believing Make It So?

Abstract: BackgroundThe large placebo effect observed in prior acupuncture trials presents a substantial challenge for interpretation of the efficacy of acupuncture. We sought to evaluate the relationship between response expectancy, a key component of the placebo effect over time, and treatment outcome in real and sham electroacupuncture (EA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…In our study, though it was not a statistically significant difference, a slightly larger percentage of patients in the SEA arm believed that they received true acupuncture, compared to the EA arm. A recent study suggested that higher response expectancy may moderate better acupuncture response in participants in patients receiving sham acupuncture, but not in patients receiving true acupuncture [38]. Therefore, it is possible that in our study a greater placebo effect may have led to better pain relief in the sham EA arm.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, though it was not a statistically significant difference, a slightly larger percentage of patients in the SEA arm believed that they received true acupuncture, compared to the EA arm. A recent study suggested that higher response expectancy may moderate better acupuncture response in participants in patients receiving sham acupuncture, but not in patients receiving true acupuncture [38]. Therefore, it is possible that in our study a greater placebo effect may have led to better pain relief in the sham EA arm.…”
Section: Discussionmentioning
confidence: 78%
“…8,24 Nocebo effects are unwanted AEs attributed to nonspecific effects. 16 Although little is known about the mechanism of the nocebo effect, research suggests that it involves different regions of brain activation and neuropeptides than does the placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a systematic review suggested that the impact of patient expectancy on acupuncture outcome is uncertain, 44 and a more recent study reported that baseline expectancy may not predict treatment response when electroacupuncture is applied. 45 Although the impact of expectancy on patient-reported outcomes may be small in this trial, lack of patient blinding may still incur positive bias on effect size. 46 Despite the lack of blinding and control for expectancy, the add-on benefits of electroacupuncture were seen in the assessorblinded objective outcomes (blinded Dellonmodified Moberg pick-up test and maximal tip pinch strength), which are known to be unaffected by a lack of patient blinding.…”
Section: Limitationsmentioning
confidence: 92%